Diffuse hemangiolymphangioma of small bowel-rare cause of obscure gastrointestinal bleeding - Rengasamy, Sudhagar; Devakumar, Murugesan Satish; Amudhan, Anbalagan; Kamalakannan, R.; Thangasamy, Selvaraj; Sathyanesan, Jeswanth (International Surgery Journal, 2022)
Hemangiolymphangioma (HL) is a rare benign tumor, commonly present in pediatric age group that involves the head and neck. Small bowel HL has been reported as solitary or segmental involvement. Here we report a case of diffuse small bowel HL, presented as chronic anemia, fatigability and obscure gastrointestinal (GI) bleeding. A 42-year male presented with 15 years history of bleeding per rectum, anemia, and fatigability, received multiple blood transfusions. The exact cause could not be identified. His complete hemogram parameters were low requiring further imaging studies. Imaging and intraoperative enteroscopy showed multiple nodular lesions in mesentry as well as in the mucosa of the entire small bowel. Bleeding points were noted in a proximal jejunal lesion which was resected. Histopathological study confirmed as benign HL. HL are rare tumors of gastrointestinal tract. To the best of our knowledge diffuse HL of the small bowel have not been reported in the medical literature. With this case scenario, one should consider these tumors in the differential diagnosis of obscure lower GI bleed and chronic anemia, as well as explore definitive management options for these benign symptomatic tumors.